2019
DOI: 10.1103/physreve.100.042142
|View full text |Cite
|
Sign up to set email alerts
|

Probability density of the fractional Langevin equation with reflecting walls

Abstract: We investigate anomalous diffusion processes governed by the fractional Langevin equation and confined to a finite or semi-infinite interval by reflecting potential barriers. As the random and damping forces in the fractional Langevin equation fulfill the appropriate fluctuation-dissipation relation, the probability density on a finite interval converges for long times towards the expected uniform distribution prescribed by thermal equilibrium. In contrast, on a semi-infinite interval with a reflecting wall at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 66 publications
3
56
1
Order By: Relevance
“…Direct simulations of macromolecular dynamics in confined domains can further enrich these studies; for example, in some simulations particles near the wall tend to stay near the wall (Chow and Skolnick, 2015), which may explain the tendency of serotonergic fibers to orient parallel to the edge immediately below the pia (for depths up to 25-50 µm; Figure 2). Finally, it has been recently demonstrated (Vojta et al, 2019) that the increased density close to a boundary arises from the non-equilibrium nature of FBM. A similar anomalous diffusion process in thermal equilibrium, modeled by the fractional Langevin equation, does not lead to accumulation at the boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Direct simulations of macromolecular dynamics in confined domains can further enrich these studies; for example, in some simulations particles near the wall tend to stay near the wall (Chow and Skolnick, 2015), which may explain the tendency of serotonergic fibers to orient parallel to the edge immediately below the pia (for depths up to 25-50 µm; Figure 2). Finally, it has been recently demonstrated (Vojta et al, 2019) that the increased density close to a boundary arises from the non-equilibrium nature of FBM. A similar anomalous diffusion process in thermal equilibrium, modeled by the fractional Langevin equation, does not lead to accumulation at the boundary.…”
Section: Discussionmentioning
confidence: 99%
“…To properly simulate chromatin diffusion within the confines of the nucleus, we added an impassable boundary to serve as a nuclear membrane. Recent work on the behavior of FBM and the fractional Langevin equation in finite volumes of space showed that the presence of boundaries and the handling of those boundary conditions can affect the long-timescale distribution close to the edges of the domain ( Guggenberger et al, 2019 ; Vojta et al, 2020 ; Vojta et al, 2019 ; Wada and Vojta, 2018 ). These studies agree with our findings that in the sub-diffusive regime, depletion occurs at the boundary ( Figure 4—figure supplement 1C, D ).…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon is consistent with previous work at thermodynamic equilibrium. Related work involved fraction Brownian motion with the reflecting boundary condition can be found in [69,70]. However, it should be noted that the observed diffusion gradients come from particle-wall effects or the preciseboundary structure, which has a different regime with the temperature gradient.…”
Section: Steady State Probability Density Function (Pdf)mentioning
confidence: 99%